Flex 4 cookbook - Noble, Joshua J., 1977- (Adobe developer library., 2010)
With this collection of proven recipes, you have the ideal problem-solving guide for developing interactive Rich Internet Applications on the Adobe Flash Platform. You'll find answers to hundreds of common problems you may encounter when using Adobe Flex, Flex 4 Framework, or Flash Builder, Adobe's GUI-based development tool. Flex 4 Cookbook has hands-on recipes for everything from Flex basics to solutions for working with visual components and data access, as well as tips on application development, unit testing, and Adobe AIR. Each recipe provides an explanation of how and why it works, and includes sample code that you can use immediately. You'll get results fast, whether you're a committed Flex developer or still evaluating the technology. It's a great way to jumpstart your next web application. Topics include: Using Spark Component Text Layout Framework Groups and Layout Spark List and ItemRenderer Images, bitmaps, videos, and sounds CSS, styling, and skinning States and Effects Working with Collections Using DataBinding Validation, formatting, and regular expressions Using Charts Services and Data Access Using RSLs and Modules Working with Adobe AIR 2.0.